2018
DOI: 10.1002/anie.201713422
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base‐Promoted Ring‐Opening 1,3‐Dioxygenation of Unactivated Cyclopropanes Using a Hypervalent Iodine Reagent

Abstract: A facile and effective system has been developed for the regio- and chemoselective ring-opening/electrophilic functionalization of cyclopropanes through C-C bond activation by [bis(trifluoroacetoxy)iodo]benzene with the aid of the Lewis basic promoter p-toluenesulfonamide. The p-toluenesulfonamide-promoted system works well for a wide range of cyclopropanes, resulting in the formation of 1,3-diol products in good yields and regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 82 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…The other one relies on electrophilic activation with Lewis acidic species. However, most of the transformations are limited to electrophilic addition reactions [9][10][11][12][13][14][15][16][17] . Ring-opening functionalization of arylcyclopropanes initiated through the single electron oxidation followed by the yield of corresponding radical cations was discovered in the 1970s 18,19 .…”
mentioning
confidence: 99%
“…The other one relies on electrophilic activation with Lewis acidic species. However, most of the transformations are limited to electrophilic addition reactions [9][10][11][12][13][14][15][16][17] . Ring-opening functionalization of arylcyclopropanes initiated through the single electron oxidation followed by the yield of corresponding radical cations was discovered in the 1970s 18,19 .…”
mentioning
confidence: 99%
“…Besides having amides as the nucleophilic partners, cyclopropylmethyl carboxylic acids, along with DBH and triphenylphosphine sulfide as the halogen source and the catalyst, respectively, could readily undergo the electrophilic bromolactonization in Markovnikov‐fashion (Scheme ) . Very recently, we successfully developed a Lewis base‐mediated ring‐opening/1,3‐difunctionalization of unactivated cyclopropanes using phenyliodane bis(trifluoroacetate) …”
Section: Methodsmentioning
confidence: 99%
“…Although non‐activated cyclopropanes are the most common three‐membered ring systems found in nature, methods for their selective ring‐opening remain scarce . Some elegant research works have recently demonstrated that they could undergo 1,3‐addition of B(C 6 F 5 ) 3 / t Bu 3 P, 1,3‐aminofluorination, 1,3‐difluorination, 1,3‐deoxygenation, and elimination reactions. Nevertheless, the development of new systems for efficient opening and functionalization of these compounds under mild and environmentally friendly conditions is still in high demand.…”
Section: Figurementioning
confidence: 99%